Latino crossings : Mexicans, Puerto Ricans, and the politics of race and citizenship - De Genova, Nicholas (Routledge, 2003)
Despite being combined in census data, there are divisions between Mexicans and Puerto Ricans in the United States. This book examines how constructions of Latino self and otherness interact with America's white/black racial consciousness.